2005
DOI: 10.1111/j.1463-1326.2005.00513.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin stimulates arterial neointima formation in normal rats after balloon injury

Abstract: The effects of hyperinsulinaemia which promote neointimal hyperplasia after balloon injury of rat carotid artery predominate over the effects which inhibit it even in normal animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…The rats were divided into 6 groups: (1) rats with blank implants and access to tap water (control = C); (2) rats with insulin implant (5 U/day) and access to glucose in their drinking water as a 40% (w/v) solution [insulin (5 U/day) + 40% oral glucose = I5G] as in Kim et al [9] but with i.p. glucose infusion (25%) to avoid any glucose lowering; (3) rats with insulin implant (4 U/day, which is similar to ∼3.9 U/day used in Foster et al [16]) and access to glucose in their drinking water as a 40% (w/v) solution [insulin (4 U/day) + 40% oral glucose = I4G]; (4) rats with insulin implant (4 U/day) and access to sucrose in their drinking water as a 10% (w/v) solution as in Foster et al [16] [insulin (4 U/day) + 10% oral sucrose = I4S]; (5) rats with blank implants and access to glucose in their drinking water as a 40% (w/v) solution (control glucose = CG), and (6) rats with blank implants and access to sucrose in their drinking water as 10% (w/v) solution (control sucrose = CS). The rats were fed a normal-fat diet, consisting of 12% fat in calories as used in Kim et al [9].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rats were divided into 6 groups: (1) rats with blank implants and access to tap water (control = C); (2) rats with insulin implant (5 U/day) and access to glucose in their drinking water as a 40% (w/v) solution [insulin (5 U/day) + 40% oral glucose = I5G] as in Kim et al [9] but with i.p. glucose infusion (25%) to avoid any glucose lowering; (3) rats with insulin implant (4 U/day, which is similar to ∼3.9 U/day used in Foster et al [16]) and access to glucose in their drinking water as a 40% (w/v) solution [insulin (4 U/day) + 40% oral glucose = I4G]; (4) rats with insulin implant (4 U/day) and access to sucrose in their drinking water as a 10% (w/v) solution as in Foster et al [16] [insulin (4 U/day) + 10% oral sucrose = I4S]; (5) rats with blank implants and access to glucose in their drinking water as a 40% (w/v) solution (control glucose = CG), and (6) rats with blank implants and access to sucrose in their drinking water as 10% (w/v) solution (control sucrose = CS). The rats were fed a normal-fat diet, consisting of 12% fat in calories as used in Kim et al [9].…”
Section: Methodsmentioning
confidence: 99%
“…We have also determined the effect of oral glucose, without insulin treatment, on neointimal growth after arterial injury. In addition, we wished to investigate the effect of oral sucrose alone and in combination with insulin, as a recently published study found that neointimal growth was actually increased in insulin-treated rats after balloon catheter injury while normoglycemia was maintained with 10% oral sucrose [16], instead of the 40% glucose in water used in our studies where insulin had a protective effect. Sucrose contains fructose, which is a known inducer of insulin resistance [17], thus we speculate that sucrose alone (the effect of which was not evaluated in the previous study) may increase neointimal growth.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies (11,20,28,39) have reported that, in at least some strains of rats, hyperinsulinemia induces a significant increase of neointima formation. Thus, an aim of our study was to verify this finding in our model.…”
Section: Infusion Of Insulin Induced Modest Hyperinsulinemia But Notmentioning
confidence: 99%
“…It is now well accepted that metabolic syndrome and type 2 diabetes are strongly associated with adverse cardiovascular events in humans, although the underlying reasons for these associations have not been clarified (3,12,44,49,55). Several recent studies have reported that hyperinsulinemia is associated with vascular remodeling and enhanced neointima formation in models of experimental vascular injury as well as in humans (20,28,37,39,55). Moreover, hyperinsulinemia, but not hyperglycemia, has been reported to induce enhanced neointima formation in models of rat vascular injury (11, 28).…”
mentioning
confidence: 99%
“…In humans with insulin resistance, the frequency of restenosis after coronary angioplasty is significantly higher than those with normal insulinemia [4]. Animals with hyperinsulinemia show increased neointima formation caused by vascular injury via potentiating smooth muscle cell migration and proliferation [5][6][7]. The application of insulin sensitizers, such as synthetic thiazolidinediones (STD), significantly reduces carotid artery intima/ media thickness in patients with type 2 diabetes [8][9][10] and in animals with induced carotid injury [11][12][13][14].…”
mentioning
confidence: 99%